Cellular repair strategies in Parkinson's disease - Winner, Beate; Vogt Weisenhorn, Daniela M.; Lie, Chichung D.; Blümcke, Ingmar; Winkler, Jürgen (Therapeutic Advances in Neurological Disorders, 2009)
Parkinson's disease (PD) is the second most common neurodegenerative disorder after Alzheimer's disease, affecting 0.7% of the elderly population (defined as over 65 years of age). PD is clinically characterized by resting tremor, muscular rigidity, hypokinesia and postural instability. These motor symptoms result largely from the deficiency or dysfunction of dopaminergic neurons in the substantia nigra. Histopathological analysis reveals depletion of dopaminergic neurons as well as eosinophilic intracytoplasmic inclusions (Lewy bodies) in surviving neurons of the substantia nigra and other brain regions. The molecular pathogenesis is linked to protein misfolding by compromised alpha-synuclein and/or related proteins (synucleinopathy). Therefore, successful therapy of motor symptoms aims for the restoration of dopaminergic neurotransmission. Pharmacological drug treatment is usually effective only at an early stage of the disease but cannot halt progressive neuronal degeneration. With recent developments in stem cell technology, cell repair or replacement approaches came into focus. Here, we review new therapeutic strategies resulting from the innate propensity of the adult brain to generate new neurons, either by pharmacological stimulation of endogenous adult stem cell population or exogenous cell transplantation modalities. © 2009, SAGE Publications. All rights reserved.
CRIS-Team Scopus Importer:2024-08-07
Keywords: Alpha-synuclein; Neurodegeneration; Neurogenesis; Stem cells; Transplantation